Comparing Iconic Memory in Children with and without Attention Deficit Hyperactivity Disorder - Nastaran Ahmadi; Mohammad Ali Goodarzi; Habib Hadianfard; Norolah Mohamadi; Daryush Farid; Golrasteh Kholasehzadeh; Mohammad Nadi Sakhvidi; Camellia Hemyari (Iranian Journal of Psychiatry, 2013)
Objective: Children with attention deficit hyperactivity disorder (ADHD) do not process most information due to inattention and loss of the opportunity to save and retrieve information. Therefore, these children experience memory impairment. Although visual memory has been previously studied in children with ADHD, iconic memory in these children has been less evaluated. We aimed to study the possibility of iconic memory impairment in children with ADHD, and compare the results with that of children without ADHD.Methods: The experimental group of this study were 6-9 year-old children who referred to the Imam Hosein Clinic and were diagnosed as having ADHD by a psychiatrist during 2011-2012 (n=30).The subjects were interviewed clinically by a psychologist; and in order to diagnose ADHD, their parents and teachers were asked to complete the child symptom inventory-4 (CSI-4). The comparison group were 6-9 year-old children without ADHD who studied in 1st and 2nd educational district of Yazd (n=30). Subjects’ iconic memory was assessed using an iconic memory task. Repeated measure ANOVA was used for data analysis. Results:Based on the iconic memory test, the mean score of ADHD children was significantly lower than that of children without ADHD (P˂0.001). Moreover, the performance of the experimental group differed significantly when the duration of the presentation differed from 50 ms to 100 ms as compared to the control group (P˂0.001). The number of correct answers increased in the experimental group as the duration of presentation increased. However, children with ADHD scored less than children without ADHD at 50 ms as well as 100 ms. The means of ADHD children increased as the duration of the presentation increased from 50 ms to 100 ms to 300 ms (P<0.001).Conclusion:Visual memory is weaker in children with ADHD, and they have weaker performance than normal children in both visual and auditory symbols at presentation durations of 50 and 100 ms. The performance of ADHD children improves as the stimulation time increases